Sensitivity of labile carbon fractions to tillage and organic matter management and their potential as comprehensive soil quality indicators across pedoclimatic conditions in Europe. (April 2019) - Bongiorno, Giulia; Bünemann, Else K.; Oguejiofor, Chidinma U.; Meier, Jennifer; Gort, Gerrit; Comans, Rob; Mäder, Paul; Brussaard, Lijbert; de Goede, Ron
Highlights: We analysed topsoils from 10 European long-term field experiments. Reduced tillage and high organic matter input increased labile soil carbon. POXC and POMC were the most sensitive to tillage and organic matter additions. POXC was highly correlated with chemical, physical and biological soil parameters. POXC has the potential to be used as a comprehensive soil quality indicator. Abstract: Soil quality is defined as the capacity of the soil to perform multiple functions, and can be assessed by measuring soil chemical, physical and biological parameters. Among soil parameters, labile organic carbon is considered to have a primary role in many soil functions related to productivity and environmental resilience. Our study aimed at assessing the suitability of different labile carbon fractions, namely dissolved organic carbon (DOC), hydrophilic DOC (Hy-DOC), permanganate oxidizable carbon (POXC, also referred to as Active Carbon), hot water extractable carbon (HWEC) and particulate organic matter carbon (POMC) as soil quality indicators in agricultural systems. To do so, we tested their sensitivity to two agricultural management factors (tillage and organic matter input) in 10 European long-term field experiments (LTEs), and we assessed the correlation of the different labile carbon fractions with physical, chemical and biological soil quality indicators linked to soil functions. We found that reduced tillage and high organic matter input increase concentrations of labile carbon fractions in soil compared to conventional tillage and low organic matter addition, respectively. POXC and POMC were the most sensitive fractions to both tillage and fertilization across the 10 European LTEs. In addition, POXC was the labile carbon fraction most positively correlated with soil chemical (total organic carbon, total nitrogen, and cation exchange capacity), physical (water stable aggregates, water holding capacity, bulk density) and biological soil quality indicators (microbial biomass carbon and nitrogen, and soil respiration). We conclude that POXC represents a labile carbon fraction sensitive to soil management and that is the most informative about total soil organic matter, nutrients, soil structure, and microbial pools and activity, parameters commonly used as indicators of various soil functions, such as C sequestration, nutrient cycling, soil structure formation and soil as a habitat for biodiversity. Moreover, POXC measurement is relatively cheap, fast and easy. Therefore, we suggest measuring POXC as the labile carbon fraction in soil quality assessment schemes in addition to other valuable soil quality indicators.